Should we be concerned about Venezuelan hemorrhagic fever? – A reflection on its current situation in Venezuela and potential impact in Latin America amid the migration crisis. (November 2021) - Rodríguez-Morales, Alfonso J.; Bonilla-Aldana, D. Katterine; Risquez, Alejandro; Paniz-Mondolfi, Alberto; Suárez, José Antonio
Abstract: Venezuelan Haemorrhagic Fever is an endemic zoonosis exhibiting a high lethality. Discovered decades ago, it is still causing seasonal hemorrhagic fever outbreaks. With the ongoing migration crisis, transmission and spreading to other countries in Latin America remains a latent threat that should be monitored, particularly in light of recent cases.